1993
DOI: 10.1111/j.1471-4159.1993.tb05857.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Two Different Forms of the Substance P Receptor in Rat Submaxillary Gland

Abstract: Studies were designed to examine the basis for the difference in molecular weights of the two proteins detected in membrane preparations of rat submaxillary glands after photolabeling with a radioactive analogue of substance P, 125I-p-benzoyl-L-phenylalanine8-substance P. When the two proteins were separated and individually digested with endoglycosidase F, the relative molecular weight of each protein was reduced by approximately 10,000, indicating that the extent of glycosylation of both proteins is the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 13 publications
5
52
1
Order By: Relevance
“…The full-length NK-1R is the predominant form expressed at sites in the human brain, whereas the truncated NK-1R is widespread throughout the central nervous system and in peripheral tissues (30). Both the long and short forms of NK-1R protein have been detected in rat submaxillary glands (31) and parotid (32). A distinct distribution of these two NK-1Rs has been observed in rat striatum, submaxillary glands, and patotid (32).…”
mentioning
confidence: 82%
“…The full-length NK-1R is the predominant form expressed at sites in the human brain, whereas the truncated NK-1R is widespread throughout the central nervous system and in peripheral tissues (30). Both the long and short forms of NK-1R protein have been detected in rat submaxillary glands (31) and parotid (32). A distinct distribution of these two NK-1Rs has been observed in rat striatum, submaxillary glands, and patotid (32).…”
mentioning
confidence: 82%
“…Although only one gene encoding the NK1 receptor has been isolated thus far (Gerard et al, 1993), the possibility exists that different forms of the receptor protein are generated from the same gene (Fong et al, 1992b;Kage et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length NK1R is the predominant form expressed at selected sites in the human brain, and truncated NK1R is widespread throughout the central nervous system and in peripheral tissues (6). Kage et al (7) reported that functional differences in two forms of NK1R present in rat submaxillary glands are caused by differences in the length of their carboxyl termini. Many studies have suggested differences in NK1R function by using an approximation of the truncated form; these studies, for the most part, however, have not used the naturally occurring variant.…”
mentioning
confidence: 99%